2022
DOI: 10.1155/2022/5211949
|View full text |Cite|
|
Sign up to set email alerts
|

Real-Time Twitter Spam Detection and Sentiment Analysis using Machine Learning and Deep Learning Techniques

Abstract: In this modern world, we are accustomed to a constant stream of data. Major social media sites like Twitter, Facebook, or Quora face a huge dilemma as a lot of these sites fall victim to spam accounts. These accounts are made to trap unsuspecting genuine users by making them click on malicious links or keep posting redundant posts by using bots. This can greatly impact the experiences that users have on these sites. A lot of time and research has gone into effective ways to detect these forms of spam. Performi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(59 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…However, in response to the state of foreign research related to this topic, I found through my research of information related to the teaching resource pathways in neonatal nursing knowledge that there are very user-friendly advanced technology use products designed specifically for neonates, as well as books, videos, websites, and domestic neonatal nursing dissemination knowledge that are taught in the same way. A search of the App Store for iPhone revealed a selection of software with English text and teaching content on baby care [17].…”
Section: Related Workmentioning
confidence: 99%
“…However, in response to the state of foreign research related to this topic, I found through my research of information related to the teaching resource pathways in neonatal nursing knowledge that there are very user-friendly advanced technology use products designed specifically for neonates, as well as books, videos, websites, and domestic neonatal nursing dissemination knowledge that are taught in the same way. A search of the App Store for iPhone revealed a selection of software with English text and teaching content on baby care [17].…”
Section: Related Workmentioning
confidence: 99%
“…For bone identification, Al-masni et al employed the YOLO model. As can be seen, the YOLO approach can produce significantly better results in medical imaging [20,21].…”
Section: Related Workmentioning
confidence: 93%
“…Studies have been conducted wherein deep learning and machine learning models were tested using dataset collected from seven countries which were impacted severely by the disease. The results revealed the superiority of the hybrid deep learning models in predicting the disease efficiently and accurately in comparison to the other state of the art approaches [37][38][39]. To implement the propagation risk analysis based on population migration, classical ML algorithms such as decision tree algorithm, random forest algorithm, adaboost algorithm, GBT algorithm, ExtraTrees algorithm, CatBoost algorithm, K-nearest neighbor (KNN) algorithm, and LightGBM algorithm are used.…”
Section: Wireless Communications and Mobile Computingmentioning
confidence: 99%